Scope and Predictors of Travel Medicine Practice among Primary Care Physicians in Qatar - Ayman Al-Dahshan (8962568) (2023)
In an era of globalization, travel-related illnesses have become a focus of public health concern. Pretravel consultation is an effective measure to promote healthy travel. This study aimed to assess the scope of primary care physicians’ (PCPs) practice of travel medicine (TM) in Qatar and its associated predictors. This was a crosssectional study design. A structured questionnaire was used to collect data from all PCPs working in the 27 primary healthcare centers in Qatar. Descriptive and analytic statistics were used as appropriate, and a multivariable logistic regression model was constructed. Three hundred sixty-four PCPs participated in the study (response rate of 89.2%). Most PCPs (91.1%) provided pretravel consultations of which 72.7% provided less than 10 consultations per month. Overall, pretravel advice content and frequency including vaccine and malaria chemoprophylaxis recommendations were inadequate. Significant predictors of high frequency of pretravel consultations (≥10/month) included male PCPs (AOR 1.78, 95% CI: 1.01, 3.18), PCPs who had postgraduate training or experience in TM (AOR 2.74, 95% CI: 1.59, 4.72), and multilingual (speaking ≥3 languages) physicians (AOR 1.96, 95% CI: 1.12, 3.45). Frequently encountered post-travel illnesses included travelers’ diarrhea, respiratory diseases, and fever. While, most PCPs provided pretravel consultations, the frequency and content of consultations were inadequate. Male PCPs, past training or experience in TM, and multilingual physicians were important predictors of providing a high frequency of pretravel consultation. The findings of this study identified several gaps in PCPs’ TM practice. Specific measures should be designed and implemented to reduce the burden of travel-related illnesses and promote healthy travel. Other Information Published in: Preventive Medicine Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.pmedr.2023.102337